Marine Conservation and Research in the Coral Triangle: The Wakatobi National Park - Richard Unsworth (2010)
Clifton J, Unsworth RKF, Smith DJ (Eds) (2010) Marine Conservation and Research in the Coral Triangle: The Wakatobi National Park?. Nova Publishers, New York (ISBN 978-1-61668-473-0) (Peer reviewed)